2017
DOI: 10.1002/lary.26772
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic immunization with human papillomavirus vaccines induces oral immunity in mice

Abstract: Objective: Although it has been shown that prophylactic vaccination can induce genital immunity, there is inadequate information on human papillomavirus (HPV) vaccine-induced oral immunity, which is of particular interest due to HPVassociated oropharyngeal malignancies and recurrent respiratory papillomatosis. Therefore, we assessed the efficacy of various HPV vaccines against oral HPV pseudovirus (PsV) infection in mice.Study Design: Preclinical scientific investigation.Methods: C57BL/6 mice were vaccinated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Preclinical studies have gone further to assess, in mice, the potential of Gardasil-4 and other candidate HPV vaccines (under development) to protect against oral HPV infections. In one study, it was demonstrated that mice intramuscularly immunized with Gardasil-4 or with a pan-HPV L2 vaccine (a candidate HPV vaccine targeting broadly neutralizing epitopes on the minor capsid) were protected from oral infection with HPV pseudovirus 16 [78]. Recently, we showed that mice orally immunized with mixed MS2-L2 VLPs (a bacteriophage-based candidate HPV vaccine composed of MS2-16L2/31L2 and MS2-Cons69-86) were protected from infection following oral infection with HPV pseudoviruses 16, 35, 39, 52, and 58 [79]; these HPV types are associated with ~80% of HPV + HNC cases.…”
Section: Prevention Of Hpv Infection and Possibly The Development mentioning
confidence: 99%
“…Preclinical studies have gone further to assess, in mice, the potential of Gardasil-4 and other candidate HPV vaccines (under development) to protect against oral HPV infections. In one study, it was demonstrated that mice intramuscularly immunized with Gardasil-4 or with a pan-HPV L2 vaccine (a candidate HPV vaccine targeting broadly neutralizing epitopes on the minor capsid) were protected from oral infection with HPV pseudovirus 16 [78]. Recently, we showed that mice orally immunized with mixed MS2-L2 VLPs (a bacteriophage-based candidate HPV vaccine composed of MS2-16L2/31L2 and MS2-Cons69-86) were protected from infection following oral infection with HPV pseudoviruses 16, 35, 39, 52, and 58 [79]; these HPV types are associated with ~80% of HPV + HNC cases.…”
Section: Prevention Of Hpv Infection and Possibly The Development mentioning
confidence: 99%
“…Two prophylactic vaccines (Gardasil-9 and Cervarix; Gardasil-4 is discontinued) are currently approved to protect against HPV infection. Gardasil-4, which protected against HPV6, HPV11, HPV16 and HPV18 has been shown to elicit oral IgG antibodies [33,34], oral antibodies neutralize/protect against HPV6, HPV16, HPV18 [35,36], and reduce oral prevalence of vaccine types (HPV types included in the vaccine) in vaccinees [37][38][39]. However, a protective effect of the vaccine on HPV types not included in the vaccine was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…The international FUTURE I/II trials showed that quadrivalent HPV vaccination provided sustained protection of 96% to 100% against anogenital condylomas and low-grade cervical and vulvovaginal neoplasias caused by HPV types 6, 11, 16, and 18. 19 Complementing the established research on genital immunity, Ahn et al 20 were the first to show that the vaccine was also effective in inducing oral immunity against HPV16 in a murine model.…”
Section: Discussionmentioning
confidence: 99%